Provider perspectives on adolescent access to contraception in South Africa - Thabile J. Ketye; Gbotemi B. Babatunde; Solange Mianda; Olagoke Akintola (AOSIS, 2024)
Background: Poor access to contraception influences adolescent health outcomes and may lead to sexual and reproductive health challenges. Unmet sexual and reproductive health should contribute to unplanned adolescent pregnancies, sexually transmitted infections, and other conditions. Therefore, it is crucial to enable adolescents to access appropriate contraceptive methods easily. Aim: This study explored factors influencing adolescents' access to contraceptive methods from the perspective of primary healthcare providers in South Africa. Setting: This study was conducted in two health districts of the Western Cape province in South Africa: the City of Cape Town Metropolitan Municipality and the West Coast district. Methods: Using a qualitative research design, in-depth semi-structured interviews were conducted with 24 healthcare providers who work in primary healthcare clinics. Subsequently, the interviews were transcribed and verified for errors. Braun and Clarke's thematic analysis model guided the data analysis using ATLAS.ti software (version 22). The study adhered to the consolidated criteria for reporting qualitative studies checklist for qualitative research. Results: Four themes emerged through the data analysis: (1) personal influences, (2) community-level influences, (3) health system influences, and (4) policy-level influences. Representative quotations were used to illustrate the themes and sub-themes. Conclusion: Adolescence is shaped by various influences that affect adolescents' ability to access contraception. These factors include their awareness of contraception, social environment, provider biases and school policies. Understanding these influences is crucial for addressing unintended pregnancies and promoting sexual and reproductive health among this age group. Contribution: This study highlights strategies that facilitate and hinder adolescents' access to contraception.